1971
DOI: 10.1071/bi9711103
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Studies with Banana Fruit Slices II. Effects of Inhibitors on Respiration, Ethylene Production, and Ripening

Abstract: Transverse slices of green banana fruit were vacuum· infiltrated with aqueous solutions of 24 potential inhibitors of protein synthesis, respiration, or ethylene production. The effects of these compounds were examined in the absence or presence of 10 p.p.m. ethylene. Of the compounds which produced marked effects mono· fiuoroacetate, 4·hydroxy·2·oxoglutarate (HKG), KCN, and cycloheximide were examined in more detail.Monofiuoroacetate (1 and 2 X 10-2M) and cycloheximide (1 and 2I-'g/ml) almost eliminated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

1974
1974
1997
1997

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In all cases, ethylene is supposed to increase the synthesis of 'new' enzymes, control organic acid concentrations based in the mitochondria, and regulate the synthesis of carotenoids in the chloroplast. However, there have been reports that the respiratory rise in the banana can occur separately from other ripening events (18). The inhibition of respiration invariably inhibited the other facets of banana ripening (particularly color change).…”
mentioning
confidence: 99%
“…In all cases, ethylene is supposed to increase the synthesis of 'new' enzymes, control organic acid concentrations based in the mitochondria, and regulate the synthesis of carotenoids in the chloroplast. However, there have been reports that the respiratory rise in the banana can occur separately from other ripening events (18). The inhibition of respiration invariably inhibited the other facets of banana ripening (particularly color change).…”
mentioning
confidence: 99%
“…On these observations it has been suggested that glycolysis is accelerated in the course of the climacteric rise in respiration (6,15,40). However, activation of glycolysis per se cannot be the cause of ripening or even of the climacteric, because anaerobiosis, while enhancing glycolysis in avocados (see below) and apples (11), prevents ripening, and uncouplers of oxidative phosphorylation, which enhance respiration and presumably glycolysis in banana slices, neither accelerate ripening nor inhibit it when ripening is induced by ethylene or occurs naturally (31,42). Furthermore, the postulated augmentation of glycolysis during the climacteric cannot be attributed to uncoupling of oxidative phosphorylation, for both the rates of 32P esterification and the levels of ATP increase during the climacteric in a variety of fruits (38,43).…”
mentioning
confidence: 99%
“…Ethylene is considered to be the agent that triggers the climacteric and fruit ripening (34). It is questionable whether protein synthesis constitutes a requisite for the climacteric rise, because the stimulation of glycolysis in preclimacteric fruits by anoxia (11), the acceleration of respiration in preclimacteric slices by uncouplers of oxidative phosphorylation (33), the demonstration of full respiratory capacity of isolated mitochondria from preclimacteric tissue (29), and the development of the climacteric under conditions which may be thought to preclude synthesis of protein (18,31,42), all indicate that the enzymatic capacity of preclimacteric fruits may be adequate to sustain the rates of respiration observed at the height of the climacteric.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19). It has been used for ripening studies in bananas (7,18,21), tomatoes (15,16,22), avocados (3,19), and apples (8,9). These studies usually involve incubating the fruit slice in an aqueous medium of the test substance.…”
mentioning
confidence: 99%